VAT AND DROPSHIPPING IN THE DIGITAL ECONOMY: A COMPARATIVE LEGAL PERSPECTIVE FROM INDONESIA, AUSTRALIA, AND SINGAPORE - Anita Cahya Pratiwi; Murwendah (Journal of Tax Policy, Economics, and Accounting (TAXPEDIA), 2025)
The development of information technology currently enables offline community activities to occur online. The internet enhances the economy via electronic business transactions. The substantial increase in internet commerce transactions corresponds with the emergence of dropshipping, a sales model intended for individuals seeking to establish a business with minimal financial investment. Unlike electronic commerce transactions, dropshipping is also subject to tax. This study employs a descriptive qualitative approach to examine and contrast the implementation of VAT in dropshipping models in Indonesia, Australia, and Singapore. The results show that VAT collection on dropshipping complies with the legal characteristics of VAT and the concept of certainty. Nonetheless, there are no explicit regulations governing dropshipping in Indonesia, thus necessitating the examination of VAT collection practices in Australia and Singapore. The Directorate General of Taxes must establish regulations for enterprises engaged in dropshipping to ensure that those liable for VAT are acknowledged as taxable entrepreneurs under VAT legislation. This study emphasizes the need to develop specific regulations in response to the expanding scale and tax potential of dropshipping, focusing on transaction mechanisms and VAT obligations to ensure compliance and legal clarity.